Pengaruh Kasadaran Wajib Pajak, Pengetahuan Wajib Pajak, Sanksi Pajak, dan Tax Amnesty Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor (Kajian Studi Literatur Manajemen Keuangan Daerah) - Ayuni Ayuni; Henny A. Manafe; M. E. Perseveranda (Dinasti Publisher, 2023)
Previous studies or appropriate studies play an important role in literature reviews or other researchers who examine the influence of variables or other factors involved in influencing a variable. This study reviews the literature review related to what factors influence motor vehicle taxpayer compliance, such as taxpayer awareness, taxpayer knowledge, tax sanctions and tax amnesty, or motor vehicle taxpayer compliance. The writing of this article aims to create hypotheses that influence each variable so that they can be used for further studies. The results obtained are that taxpayer awareness has a positive or important effect on motor vehicle taxpayer compliance, taxpayer knowledge has a positive or important effect on motor vehicle taxpayer compliance, tax sanctions have a positive or important effect on motor vehicle taxpayer compliance, and tax amnesty has a positive or important effect on motor vehicle taxpayer compliance.